2014
DOI: 10.1057/fsm.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Do investors show an attentional bias toward past performance? An eye-tracking experiment on visual attention to mutual fund disclosures in simplified fund prospectuses

Abstract: His research focus on media psychology and media effects, persuasion, emotions, and empirical methods in the field of political communication, mobile communication, online communication and financial communication.ABSTRACT This study examines the cognitive processes underlying investors' extrapolations of past fund performance and whether investors' attention patterns may explain their return-chasing behaviors. We measured the attention that investors paid to mutual fund disclosures in a simplified fund prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 121 publications
1
18
0
Order By: Relevance
“…The greater attention dedicated to the minor AOI represented by the last years of the Past performance is in line with a financial perspective which considers them important as they refer to a crucial time period: in fact, the product’s trend across the most recent years usually affect investors’ decision making through inducing a recency (or end-anchoring) bias. Our results corroborate previous findings in neurofinance which demonstrate an attentional bias toward the last portion of a graph which displays financial assets past performances (Hüsser and Wirth, 2014; Duclos, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The greater attention dedicated to the minor AOI represented by the last years of the Past performance is in line with a financial perspective which considers them important as they refer to a crucial time period: in fact, the product’s trend across the most recent years usually affect investors’ decision making through inducing a recency (or end-anchoring) bias. Our results corroborate previous findings in neurofinance which demonstrate an attentional bias toward the last portion of a graph which displays financial assets past performances (Hüsser and Wirth, 2014; Duclos, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Visual attention is a scarce resource, cognitive effortful and selective: a continuous automatic competition occurs among visual stimuli, to speed up the representation of the observed object (or text, picture) in the visual cortex. Since previous research on visual attention demonstrated that pictorial information grabs greater attention than text (Rayner et al, 2001), some researchers, like Hüsser and Wirth (2014), explored the effects of converting the narrative description of investment philosophy into a graphic representation. They quantified the attention dedicated to the investment philosophy comparing it to the time taken by the same subjects to explore the graphical representation of the fund past performance, observing that the former attracted less attention than the latter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of different biases on the different determinants of investor behavior such as risk perception (Wang et al, 2006;Riaz and Hunjra, 2015), risk propensity (Pan and Statman, 2012), portfolio analysis (Hoffmann et al, 2010) risk tolerance (Sulaiman, 2012; Pak and Mahmood, 2015), financial rationality (Soufian et al, 2014), financial literacy Omark, 2015, financial planning (Guillemette et al, 2015;Hayat and Anwar, 2016) and financial personality (Kubilay and Bayrakdaroglu, 2016). The following factors have been identified, which implies a significant impact on the investors' decisions such as investor's experience (Feng and Seaholes, 2015;Papadovasilaki, 2015), past investment results (Ray, 2009;Olsen, 1998), occupational effects (Dhar and Zhu, 2006;Yee et al, 2010), timing of security issue (Deng et al, 2012;Maung and Chowdhury, 2014), investment intentions (Njuguna et al, 2016;Trang and Tho, 2017), information processing (Graham et al, 2002;Hüsser and Wirth, 2014), emotional feelings (Hassan and Bashir, 2014;Charles and Kasilingam, 2015).…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Most of the data are presented in tabular format; the sole exception is that a bar chart of annual returns over the previous 7 years is mandated-and the specifications for those charts are poorly designed and may not depict the most helpful information (Figure 1). When researchers assessed how people used this chart, they found that viewers focused on unhelpful information and relied on irrelevant data, leading to poor decision-making (Hüsser & Wirth, 2014).…”
Section: Introductionmentioning
confidence: 99%